Kelas Rasa Usaha: Pemberdayaan Siswa Melalui Edupreneurship Produk Kuliner dalam Pembelajaran Vokasi - Khotimah, Ika Khusnul; Komiyati, Komiyati; Sukoco, Yusab; Johanda, Ronit; Yulia, Arie Ludfianti; Kuat, Tri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The general objective of this scientific work is to provide a comprehensive overview of student empowerment through culinary entrepreneurship activities in the school environment. This study uses a descriptive qualitative approach. The subjects of the research are vocational high school students participating in the 'Taste of Entrepreneurship Class' program, culinary productive teachers, and the head of the vocational program. Data were collected using several techniques, namely participatory observation, in-depth interviews, and documentation. Data analysis was conducted using the interactive model according to Miles and Huberman, which includes three stages: data reduction, data presentation, and conclusion/verification. The results of the analysis show that the integration of edupreneurship in vocational education not only produces graduates who are job-ready, but also ready to create job opportunities, possessing independent, creative characteristics, and high competitiveness in facing the dynamics of industry and global challenges.